Facilitated Extinction Training to Improve Pharmacotherapy for Smoking Cessation: A Pilot Feasibility Trial. Issue 10 (12th September 2017) - Brandon, Thomas H; Unrod, Marina; Drobes, David J; Sutton, Steven K; Hawk, Larry W; Simmons, Vani N; Brandon, Karen O; Roetzheim, Richard G; Meltzer, Lauren R; Miller, Ralph R; Cahill, Shawn P
Abstract: Introduction: Varenicline reduces smoking satisfaction during the pre-cessation run-in period, which may contribute to extinction of cravings and smoking behavior. Research indicates that efficacy is enhanced when the run-in period is increased from 1 to 4 weeks, providing a longer extinction opportunity. We hypothesized that efficacy could be further enhanced by harnessing basic and applied research on extinction. We developed a pre-cessation extinction-facilitating intervention and tested its feasibility in a pilot trial. Methods: The facilitated extinction (FE) intervention comprised brief counseling and workbook-recommending strategies to maximize extinction processes during the run-in, including instructions to smoke at a normal rate across contexts and cues, and use of an extinction cue to enhance generalization. Participants were randomly assigned to one of three varenicline interventions: standard (1-week run-in), extended (4-week run-in), and extended + FE. Interventions were delivered prior to the target quit date (TQD). Assessments were conducted in weeks 1 and 4 pre-TQD and 1 and 3 months post-TQD, with focus on feasibility indices. Results: Recruitment and retention goals were met ( N = 58). Treatment satisfaction was high across groups. The majority of FE participants adhered to instructions and maintained their usual smoking rate during the run-in period. Greater decreases in craving and smoking satisfaction were observed among participants in both extended groups versus the standard group ( p < .005). Conclusions: Feasibility was demonstrated. Participants adhered to the FE intervention, thereby optimizing the number and variety of extinction trials. Findings support testing the novel FE smoking cessation intervention in a fully powered trial. Implications: This study expands the research on the clinical benefits of extending the pre-cessation run-in period of varenicline. It introduces the hypothesis that further benefit might be achieved by translating basic behavioral research, as well as cue-exposure research and therapy for other disorders, to improve the extinction and generalization processes thought to underlie much of varenicline's effect. A FE intervention was developed and found acceptable to smokers and feasible to implement in a research setting. The study sets the stage for a subsequent randomized controlled trial.